A Pragmatic Analysis of Muharikah’s Novel Sayang yang Tak Terungkap (2023) - Muhammad Danial; Ayu Melati Ningsih; Vera Kristiana (UIN Salatiga, 2026)
This research examined the politeness strategies employed by the protagonist, Iman Syahirah, in Sayang yang Tak Terungkap (2023), a Malaysian Islamic novel written by Muharikah. Using Brown and Levinson’s (1987) politeness theory through a pragmatic analysis, the study identifies and interprets the characters' expressions within diverse social and professional settings. Using a qualitative descriptive method along with documentation and content analysis techniques, the research identifies and interprets the character's expressions within diverse social and professional settings. The results indicate that Iman Syahirah utilizes all four categories of politeness strategies—positive politeness, negative politeness, bald on-record, and off-record. Positive politeness fosters solidarity and empathy among patients and colleagues, whereas negative politeness indicates caution, respect, and an understanding of social distance. The bald-on-record approach emphasizes professional confidence and ethical power, while off-record reflects delicate communication consistent with cultural and religious awareness. These results suggest that politeness in this Islamic novel serves not merely as a linguistic tactic but also as a representation of gender beliefs, power dynamics, and Islamic principles in the Malay-Islamic community. As a result, this research adds to the domain of literary pragmatics by combining linguistic examination with social context and religious identity in depicting a professional Muslim woman.